Negative impact from the application of natural fibers. (1st February 2017) - Adekomaya, Oludaisi; Jamiru, Tamba; Sadiku, Rotimi; Huan, Zhongie
Abstract: Natural fibre reinforced composites have been widely explored in many engineering applications in recent times due to its comparative advantages in terms of recyclability and sustainability. Of most interest in many engineering applications is its ability to offer lighter weight component as against synthetic and metallic materials. In recent times, metallic and synthetic materials are currently being replaced in many automobiles industries while natural fibre reinforced composites continue to enjoy reasonable patronage in this industry. In this study, the overall application of natural fibre was discussed with focal point on global consumption of natural fibre in automobile industries and its attendant implication on the environment and biodiversity. Part of the conclusions drawn from this study emphasised the need to preserve the nature from impending extinction.